Manajemen Program Keagamaan dalam Membangun Religiusitas Peserta Didik - Moh Hanif Adzhar; Zahrotunnisa` Siswahyuningsih (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This research aims to comprehensively describe the role of religious program management in fostering religiosity, including the values and character of students at YPI Ar-Rahman in Kediri City, with a focus on planning, implementation, and evaluation. The research design used is a descriptive qualitative approach with a case study methodology, which involves an in-depth examination of phenomena. The research results indicate that the religious program is systematically designed through coordination between the RKT and KSP teams, with main programs such as Dhuha prayer, congregational Zuhr prayer, and Wafa completing Quran reading and writing. The implementation of the program receives full support from teachers and the foundation, and demonstrates active student involvement. Teachers' exemplary behavior was proven to have a strong impact on students' religious motivation. Program evaluations were conducted periodically to adjust implementation to students' academic needs. Through structured, flexible religious programs supported by good role models and evaluation, students' religious character can be optimally developed. Based on these implications, religious programs are contextually considered as a medium for incubating the religious character of students in educational institutions.